Seismic performance of full-scale precast non-seismic beam-column joints with corbels under in-plane lateral cyclic loading / Kay Dora Abd Ghani - Abd Ghani, Kay Dora (Institute of Graduate Studies, UiTM, 2015)
Precast concrete building had been widely used in Malaysia for the public amenities such as residential housings, shopping complexes, hospitals, and school buildings. Moreover, most of the precast concrete buildings in Malaysia were designed in accordance to British Standard (BS8110) which has no specific detailing design of joint for precast elements under seismic loading. Thus, this study aims to evaluate the behavior of non-seismic designed precast buildings when subjected to long-distant earthquakes from Sumatera and near-field earthquakes. Three sub-assemblages of the specimens consisting of corner, interior and exterior of precast beam-column joints, were designed, constructed and tested under reversible in-plane lateral cyclic loading. These sub-assemblages were representing the main joints in the prototype precast two storey school building. Direct Displacement-Based Design (DDBD) approach was utilized in developing load versus displacement curve (hysteresis loops) for all three sub-assemblages studied. Subsequently, the exterior beam-column joint was retrofitted using Carbon Fiber Reinforced Polymer (CFRP) wrapping and steel plate bonding. Ruaumoko Programming was utilized in modeling the inelastic behavior of the joints and overall structural deformation of the school building. The hysteresis loops of the precast beam-column joints were modeled using Hysteres program. The behavior of prototype school building was analyzed using Ruaumoko 2D and the mode shapes of the structural failure were illustrated by using Dynaplot program. In addition, a seismic assessment under Performance Based Earthquake Engineering (PBEE) was carried out using the fragility curve based on the Design Basis Earthquake (DBE), Maximum Considered Earthquake (MCE) and four past earthquake records…